2007
DOI: 10.1590/s0103-64402007000400005
|View full text |Cite
|
Sign up to set email alerts
|

Periradicular repair after two-visit endodontic treatment using two different intracanal medications compared to single-visit endodontic treatment

Abstract: The number of appointments necessary to treat infected root canals is one of the most controversial issues in endodontics. This study evaluated, in dogs, the response of the periradicular tissues to the endodontic treatment of infected root canals performed in a single visit or in two visits, using different interappointment dressings. Periradicular lesions were induced by inoculating Enterococcus faecalis in the root canals. After confirming that a periradicular lesion developed, the root canals were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 15 publications
(23 reference statements)
1
44
1
6
Order By: Relevance
“…This combination has already been demonstrated to exhibit pronounced antibacterial activity against several candidate endodontic pathogens (13,14,16). Although CPMC exhibits high toxicity when used alone, satisfactory biocompatibility results have been observed for its association with CH in animal studies (17,18). Clinical studies evaluating the incidence of postoperative pain (19), antibacterial activity (3) and treatment outcome (20) have demonstrated excellent results when using an antibacterial protocol for treatment that includes a 7-day interappointment medication with CHPG.…”
Section: Discussionmentioning
confidence: 99%
“…This combination has already been demonstrated to exhibit pronounced antibacterial activity against several candidate endodontic pathogens (13,14,16). Although CPMC exhibits high toxicity when used alone, satisfactory biocompatibility results have been observed for its association with CH in animal studies (17,18). Clinical studies evaluating the incidence of postoperative pain (19), antibacterial activity (3) and treatment outcome (20) have demonstrated excellent results when using an antibacterial protocol for treatment that includes a 7-day interappointment medication with CHPG.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that higher concentrations of NaOCl possess a greater irritation effect on the apical cells and periapical tissues (38). Silveira et al have shown that 2.5% NaOCl solution and 2% chlorhexidine completely remove bacterial infection of E. faecalis after 30 s of contact (39).…”
Section: Raspravamentioning
confidence: 99%
“…4,5 The filling technique and the properties of the material employed are the two essential factors for three-dimensional filling of the root canal system. [6][7][8] It has been suggested that the ideal root canal filling should consist of a sufficient amount of gutta-percha covered by a thin layer of a sealer.…”
Section: Introductionmentioning
confidence: 99%
“…One of these devices was the Obtura II system, which heats and injects the plasticized gutta-percha into the canal 5 . Karr et al 21 and Karabucak et al 22 observed that both Resilon and Obtura gutta-percha showed similar results when lateral grooves and dentin depressions were filled using the Obtura II system.…”
Section: Introductionmentioning
confidence: 99%